Structural design of memory system for Ternary Optical Computer. - Honghong Zhang; Yi Jin; Hongjian Wang; Xunlei Chen; Zhehe Wang; Shan Ouyang; Shuang Li (PLoS ONE)
Ternary Optical Computer (TOC) is unique in the development of optical computers, in terms of principle, experiment, algorithm and application. After 20 years of development, six generations of prototypes have been developed. At present, tri-state optical signal storage is the main problem faced by TOC. According to the characteristics of tri-state optical signals and the ternary optical processor's special requirements for storage systems, we design and implement the interface structure of TOC memory system, including the overall structure of the interface, the address generation module for memory access, the data input and output channels, the read/write timing, and the working process of the memory interface. Finally, the correctness of the memory system interface design is verified by the experiments, which are carried out on FPGA, of reading and writing operational result data of the SD16 TOC prototype. This work tries to improve the theoretical system and practical basis of TOC.